The Bowen–Conradi syndrome protein Nep1 (Emg1) has a dual role in eukaryotic ribosome biogenesis, as an essential assembly factor and in the methylation of Ψ1191 in yeast 18S rRNA - Meyer, Britta (Oxford University Press, 2011)
The Nep1 (Emg1) SPOUT-class methyltransferase is an essential ribosome assembly factor and the human Bowen–Conradi syndrome (BCS) is caused by a specific Nep1(D86G) mutation. We recently showed in vitro that Methanocaldococcus jannaschii Nep1 is a sequence-specific pseudouridine-N1-methyltransferase. Here, we show that in yeast the in vivo target site for Nep1-catalyzed methylation is located within loop 35 of the 18S rRNA that contains the unique hypermodification of U1191 to 1-methyl-3-(3-amino-3-carboxypropyl)-pseudouri-dine (m1acp3Ψ). Specific (14)C-methionine labelling of 18S rRNA in yeast mutants showed that Nep1 is not required for acp-modification but suggested a function in Ψ1191 methylation. ESI MS analysis of acp-modified Ψ-nucleosides in a Δnep1-mutant showed that Nep1 catalyzes the Ψ1191 methylation in vivo. Remarkably, the restored growth of a nep1-1(ts) mutant upon addition of S-adenosylmethionine was even observed after preventing U1191 methylation in a Δsnr35 mutant. This strongly suggests a dual Nep1 function, as Ψ1191-methyltransferase and ribosome assembly factor. Interestingly, the Nep1 methyltransferase activity is not affected upon introduction of the BCS mutation. Instead, the mutated protein shows enhanced dimerization propensity and increased affinity for its RNA-target in vitro. Furthermore, the BCS mutation prevents nucleolar accumulation of Nep1, which could be the reason for reduced growth in yeast and the Bowen-Conradi syndrome.